2013
DOI: 10.1080/17441692.2012.758299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biogas digesters on wood utilisation and self-reported back pain for women living on rural Kenyan smallholder dairy farms

Abstract: Women living on rural Kenyan dairy farms spend significant amounts of time collecting wood for cooking. Biogas digesters, which generate biogas for cooking from the anaerobic decomposition of livestock manure, are an alternative fuel source. The objective of this study was to quantify the quality of life and health benefits of installing biogas digesters on rural Kenyan dairy farms with respect to wood utilisation. Women from 62 farms (31 biogas farms and 31 referent farms) participated in interviews to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In Mukurwe-ini, a convenient sampling method was used for logistical reasons, as the research was conducted alongside another project (Dohoo et al 2012(Dohoo et al , 2013. The other project included 32 farms with biogas digesters recently constructed on the farm by a non-governmental organisation and a reference group of 32 randomly selected farms without biogas digesters in the region, matched on age of the participant, family size, and number of cows.…”
Section: Selection Of Study Area Farms and Animalsmentioning
confidence: 99%
“…In Mukurwe-ini, a convenient sampling method was used for logistical reasons, as the research was conducted alongside another project (Dohoo et al 2012(Dohoo et al , 2013. The other project included 32 farms with biogas digesters recently constructed on the farm by a non-governmental organisation and a reference group of 32 randomly selected farms without biogas digesters in the region, matched on age of the participant, family size, and number of cows.…”
Section: Selection Of Study Area Farms and Animalsmentioning
confidence: 99%
“…This large number of hours cooking with biogas was expected because a related study showed that two cows fueling a digester reduced wood consumption for a family of four by approximately 44%. 9 When comparing the seasonal variation in time spent cooking with wood (Figure 2), the women spent similar amounts of total time cooking with wood, however, cooking with biogas increased by about 147% from February to June/July. There are at least two possible reasons for this increase in biogas cooking time.…”
Section: Discussionmentioning
confidence: 91%
“…[8][9][10][11][12] Biogas digesters represent an alternative renewable energy technology that has been identified as one of the most energy-efficient and environmentally beneficial technologies for bioenergy production. 13 Biogas digesters anaerobically decompose organic material, such as livestock waste, to produce high methane (CH 4 )-content combustible gas that burns cleanly and at high temperatures, which can be used for cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting biogas technology has been shown to help improve rural livelihoods by: reducing costs associated with the purchase of firewood and chemical fertilizers; improving air quality [28] and health outcomes [29] and by reducing smoke from cooking and minimizing emissions from burning biomass; reducing the workload of women who no longer need to collect firewood, tend fires and clean the soot from cooking utensils; and diminishing manure smells where animal housing is located [30].…”
Section: Livelihood Improvementsmentioning
confidence: 99%